2008
DOI: 10.3382/ps.2007-00266
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Enzyme Supplementation and Heat Processing of Barley on Digestive Traits and Productive Performance of Broilers

Abstract: We studied the influence of enzyme supplementation (ES) of the diet and heat processing (HP) of barley on digestive traits and productive performance of broilers from 1 to 42 d of age. There were 6 diets arranged factorially with 2 doses (0 and 500 ppm) of a fungal enzyme complex with beta-glucanase and xylanase activity and 3 HP of barley (raw, micronized, and expanded). In addition, a control diet based on raw corn without ES was also included from 1 to 21 d of age. Enzymes reduced intestinal viscosity (IV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 34 publications
9
40
2
3
Order By: Relevance
“…These results are consistent with other studies that reported higher weight gain in 42-d-old broilers fed diets with multiple enzyme complexes (Figueiredo et al, 1998;West et al, 2007;García et al, 2008;Farran et al, 2010;Tiwari et al, 2010;Iwahashi et al, 2011).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with other studies that reported higher weight gain in 42-d-old broilers fed diets with multiple enzyme complexes (Figueiredo et al, 1998;West et al, 2007;García et al, 2008;Farran et al, 2010;Tiwari et al, 2010;Iwahashi et al, 2011).…”
Section: Resultssupporting
confidence: 93%
“…Previous studies reported improvements in weight gain, feed-togain ratio, and carcass traits of broilers supplemented with exogenous enzyme complexes (García et al, 2008;Boguhn and Rodehutscord, 2010;Farran et al, 2010;Campasino et al, 2015). Different strategies for enzyme utilization are applied (decreasing nutrient specifications or assigning nutrient values to the enzymes) when combining two enzyme products (Avila et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The result of the current experiment is in agreement with Afsharmanesh et al (2008) who reported that heat treatment (oven dried at 808C for 15 h) significantly improved FCR and AME, protein and P digestibility and destroyed endogenous phytase and xylanase in wheat-based diets, also increasing the levels of soluble NSP. Steam HP of cereal may modify the physical and chemical structure of the cereal, improving accessibility of enzymes to dietary components and facilitating its utilisation (Gracia et al 2008). Zaghari (2006) reported that autoclaving of wheat increased its amino-acid digestibility.…”
Section: Carcassmentioning
confidence: 99%
“…Gracia et al (2003) reported that HP of wheat improved body weight gain (BWG) in broilers in the early stages of growing and that the beneficial effects of HP disappeared with age. HP of wheat modifies the physical and chemical structure of the cereal, improving accessibility of enzymes to the dietary components and facilitating its utilisation (Gracia et al 2008). Plavnik and Sklan (1995) reported that dry extrusion of barley increases the AME of diets by 2.2%.…”
Section: Introductionmentioning
confidence: 99%
“…Barley and wheat contain variable amounts of non-starch polysaccharides (NSP) which increase digesta viscosity and reduce nutrient absorption and performance in broilers (Edney et al, 1989;Wang et al, 2005;García et al, 2008) and laying hens (Lázaro et al, 2003;Mirzaie et al, 2012). In layers, a high NSP content of the diet is associated with an increase in dirty eggs (Francesch and Brufau, 2004).…”
Section: Introductionmentioning
confidence: 99%